(untitled) (Singapore,River Edge, NJ, 1993)
The papers collected in this book were invited by the editors as tutorial courses or keynote speeches for the Fourth International Conference on Software Engineering and Knowledge Engineering. The book offers wide coverage of the main topics involved with the specifications, prototyping, development and maintenance of software systems and knowledge-based systems. The main issues in the area of software engineering and knowledge engineering are addressed and for each analyzed topic the corresponding research state is reported.
Keywords: Software engineering,Expert systems (Computer science),Computer software,Công nghệ phần mềm,Chuyên viên hệ thống,Phần mềm máy tính; Development,Phát triển